From Person-Days Lost to Labour Militancy: A New Look at the Canadian Work Stoppage Data - Briskin, Linda (Relations industrielles / Industrial Relations, 2007)
Using the micro-data from Human Resources and Social Development Canada (HRSDC) on the 23,944 stoppages in Canada between 1960 and 2004, this article introduces a labour militancy perspective on work stoppages, that is, from the point of view of workers. It explores patterns of militancy with a focus on strike duration, strike size and strikes for first contracts, and supports re-interpretations which help make visible the significance of such stoppages for workers, unions and communities. A labour militancy frame presents an alternative to the employer perspective on time lost, the government concern to measure the economic impact of stoppages, and the scholarly emphasis on strike determinants. As part of re-examining the HRSDC work stoppage data from a labour militancy perspective, the paper considers the source of these data. It juxtaposes the statistical data with interviews with the provincial correspondents who collect the information for HRSDC. Examining the data in this light underscores the political nature of data collection (what is seen to be germane and not), data presentation (what is made visible and what is not), and data sources (whose voices are heard).